Assessing the performance of public hospitals using the EFQM Excellence Model Case study: Tishreen University Hospital in Lattakia - زهرة فاتنة; كندة ديب; جميل عيسى (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the research is to identify the level of performance of Tishreen University Hospital in Lattakia using the European Excellence Model EFQM, the researcher relied on the deductive approach as a general method. She follows a descriptive analytical method. To achieve the objectives of the research, a questionnaire was developed and distributed to a sample of Director’s assistants, department heads, doctors, nurses and hospital staff, and then appropriate statistical analyzes were conducted on it. The most important results that were reached: The performance at Tishreen University Hospital-from the point of view of the research sample-in light of the European Excellence Model EFQM, achieves a high level according to the fifth Likert scale. In light of the research finding, the researcher proposes the following: Increased interest in and commitment to and promotion of all EFQM standards of excellence; To help develop the hospital, and support it to provide excellent health services.